Clinical value of the expression levels of protein tyrosine phosphatase non-receptor type 22.6 mRNA in peripheral blood mononuclear cells in Crohn’s disease - Hu, Mei; Chen, Zhitao; Liao, Yusheng; Wu, Jie; Zheng, Dan; Zhang, Heng (Clinical and experimental immunology, 2022)
To explore the relationship between the expression levels of protein tyrosine phosphatase non-receptor type (PTPN) 22.6 mRNA in peripheral blood mononuclear cells (PBMCs) and the disease activity as well as clinical characteristics in Crohn's disease (CD) patients. A total of 480 subjects were enrolled. Data were collected including baseline information, expression levels of PTPN22.6 mRNA in PBMCs for all subjects, C-reactive protein (CRP) levels in serum, clinical characteristics, and disease activity for all patients. Expression levels of PTPN22.6 mRNA in PBMCs, CRP levels in serum, clinical characteristics according to Montreal Classification [8], and Crohn's disease activity index (CDAI) were the primary observation outcomes. The expression levels of PTPN22.6 mRNA (P = 0.032) in PBMCs and serum CRP levels (P < 0.001) were significantly higher in active CD patients than in inactive CD patients (P = 0.032). Correlation analysis showed that there was a positive correlation between expression levels of PTPN22.6 mRNA and CDAI value (r = 0.512, P = 0.003), as well as expression levels of PTPN22.6 mRNA and CRP levels in the CD group (r = 0.456, P = 0.006). There were significantly higher expression levels of PTPN22.6 mRNA in PBMCs in patients with structuring behavior than that in patients with non-stricturing and non-penetrating (NSNP) behaviors (P = 0.018) and penetrating behaviors (P = 0.024). The expression levels of PTPN22.6 mRNA can be used as an indicator to help predict CD diagnosis, disease activity, serum CRP level, and behavior type of CD disease.